TINDAK PIDANA PERKOSAAN TERHADAP PEREMPUAN PADAHAL DIKETAHUI DALAM KEADAAN PINGSAN YANG DILAKUKAN SECARA BERSAMA-SAMA (PUTUSAN NOMOR 92/PID.B/2021/PN JKT.UTR): Crime Of Rape Woman Though Known to be in a State Unconsciousness Committed Jointly (Decision Number 92/Pid.B/2021/PN Jkt.Utr) - Nadya Tri Astuti; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2024)
The crime of rape against women is an act of two or more people committing rape against a woman outside of marriage even though the woman is known to be unconscious. The problems in this research are, Is Judge’s Decision Number 92/Pid.B/2021/PN Jkt.Utr in the crime of rape against the victim appropriate or not based on Article 285 of the Criminal Code?, What are the categories of participation in the crime of rape committed jointly in Decision Number 92/Pid.B/2021/PN Jkt.Utr. This research uses a normative research type with secondary, analytical descriptive data which is analyzed qualitatively by drawing conclusions deductively. The result and conclusions, That Judge’s Decision Number 92/Pid.B/2021/PN Jkt.Utr is not appropriate based on Article 285 of the Criminal Code because the victim’s helplessness was not caused by the perpetrator’s actions, but rather the victim was unconscious due to being very drunk. Category of participation in case Decision Number 92/Pid.B/2021/PN Jkt.Utr is a from of participation in the crime of rape. This is because there is conscious cooperation and physical cooperation or implementation carried out by the perpetrator. Pperpetrator may be subject to Article 286 of the Criminal Code in conjunction with Article 55 1 of the Criminal Code.